Model Transformational Service Dengan Pendekatan Teori Sistem Interpersonal Imogene King Terhadap Mutu Pelayanan Kesehatan Dipuskesmas Tanjung Palas Kabupaten Bulungan Kalimantan Utara Tahun 2018 - Indah Nursanti; Muhammad Hadi; Rochadi Haryanto (Poltekkes Kemenkes Surakarta, 2018)
AbstrackBackground : There are issues that Health Center is still considered as a middle to lower health service, unsatisfactory service, and the attitude of officers who arbitrarily provide services that cause the Health Center got a bad view. Observations on 5 nurses were still found the nurses who were still passive towards work, rarely smiled, and did not care about their appearance. Transformational service as a service at the highest level that is expected to be able to change customer character because it is able to provide solutions to customer problems. Purpose: The purpose of this study was to know the Transformational Service with Imogene King interpersonal system approach and the effect to the quality of health service at Tanjung palas Health Center, Bulungan District, North Kalimantan in 2018 2018. Method: This was a quantitative study with a quasi-experimental research method with pre-post and control group design. The sample of this study were patients at Tanjung Palas Health Center and Bumi Rahayu Health Center, with total sample in the intervention group were 40 respondents and in the control group were 40 respondents, used a simple random sampling technique and analysis method of General Linear Model Repeated Measure (GLM-RM). Result: The results of this study showed that there were significant figures at the level of health services at Tanjung Palas Health Center. The mean values from measurement 1 to 4 were 76.20 from measurements 1 and d 88.29 in measurement 4 with a difference of 12.09. While the average value in the control group between measurements 1 and 4 were 75.93 and 83.44 with a difference of 07.51. From the difference in the average value between the differences in quality of health services in measurements 1 and 4 in the intervention group compared to the control group made conclusion that Ha accepted. Conclusion: The Transformational Service model with Imogene King interpersonal system approach was effective to improve the quality of health service at Tanjung palas Health Center, Bulungan District, North Kalimantan in 2018. Conclusion : The Transformational Service model with Imogene King interpersonal system approach was effective to improve the quality of health service at Tanjung palas Health Center, Bulungan District, North Kalimantan in 2018.